ENERGY SUPPLY OF COMMERTIAL GREENHOUSE WITH THE GAS DRIVEN HEAT PUMP part II - Sit M.L.; Ioisher A.A.; Andronaty N.R.; Burciu V.I.; Sit B.M. (Problems of the Regional Energetics, 2013)
In this article a scheme of connection of heat exchanger for utilization of heat of flue gases to evaporator is proposed. In proposed scheme is ensured the minimum power of ventilator for air’s feeding to the evaporator of heat pump and compensation of pulsations of temperature of flue gases and pressure of ventilator. It is shown how to optimize parameters of heat exchanger in conditions of minimum of dissipation of energy with utilization of value of entransy. It is elaborated a scheme of coordinated control system of hydraulic transmissions, that transfers power on compressor of heat pump and electrical generator.